Anna Rocca and Kenneth Reeds, eds. Women Taking Risks in Contemporary Autobiographical Narratives. Newcastle: Cambridge Scholars, 2013. 232 pp. - Kate Averis (Studies in 20th & 21st Century Literature, 2015)
Review of Anna Rocca and Kenneth Reeds, eds. Women Taking Risks in Contemporary Autobiographical Narratives. Newcastle: Cambridge Scholars, 2013. 232 pp.
Keywords: risk-taking; autobiography; life-writing; testimonial writing; women writers; gender; Francophone